Influence of Copigmentation and Encapsulation on Stability and Antioxidant Activity of Anthocyanins from Blue and Pink Cornflower (Centaurea cyanus L.) Flowers - Aleksandra Popowska; Joanna Oracz (Molecules)
The aim of this study was to determine the optimal conditions for copigmentation and encapsulation of anthocyanins extracted from blue and pink cornflower (Centaurea cyanus L.) flowers and to produce encapsulates resistant to environmental factors. Extracts rich in anthocyanins were encapsulated using spray-drying and sublimation techniques. Baicalin and chlorogenic acid were successfully used as copigmentation agents for blue and pink cornflower anthocyanins. The extracts and encapsulates obtained were subjected to stability tests to assess the stability of color and changes in total anthocyanins content, total phenolic compounds content, and antioxidant activity under exposure to high temperature and UV radiation. The developed encapsulation method effectively protects anthocyanins from adverse environmental conditions. The obtained preparations were characterized by a high content of anthocyanins and phenolic compounds as well as a strong antioxidant potential. The highest stability was demonstrated by anthocyanin encapsulates isolated from the pink flowers of the cornflower, obtained by spray-drying with the addition of a copigment (chlorogenic acid or baicalin) and with a weight ratio of anthocyanin extract to carrier of 1:10. The results of this study suggest that anthocyanin preparations from cornflower, after encapsulation and copigmentation with baicalin or chlorogenic acid, can be used as stable colorants in the food industry as well as functional ingredients providing high levels of antioxidant activity.